Pengaruh Kemampuan dan Motivasi Terhadap Kinerja Anggota DPRD Kota Banjarmasin - ., Nurhikmah (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2018)
The good performance of the legislature in this autonomy era is a necessity and necessity so that the institution can carry out its duties, authority and rights accountably, be more responsive and reliable. Good performance is certainly influenced by ability, leadership and work motivation and discipline of the board members themselves. On the basis of these reasons the authors are interested in discussing and knowing how the Effect of Ability and Motivation on the Performance of Banjarmasin City DPRD Members. This study aims to be able to describe the ability, work motivation and performance, then analyze the influence of work ability and motivation on the performance of Banjarmasin City DPRD Members then analyze the influence of the dominant variables between work ability and motivation dominant influence on the performance of Banjarmasin City DPRD Members.The analytical tool used in this study is to use used validity and reliability testing tools for the data, reliability testing was carried out by Cronbach Alpha test. To find out the influence between Ability (X1), Motivation (X2) and Performance (Y), simultaneous regression analysis methods are used as follows: Ability Test Results (X1), Motivation (X2) on Performance (Y) simultaneously on DPRD Members Banjarmasin. The analysis used is Linear Regression and tested using a distribution table.Based on the results of the research results, it can be stated that simultaneously it is known that for Ability t count = 2.914 *> t (45; 0.05) = 1.679 is significant and for Motivation t count = 0.944ns <t (45; 0.05) = 1.679 which means that work ability has a significant effect on the performance of Banjarmasin City DPRD members, while non-significant work motivation means ability and motivation can affect performance even though there are motivational variables that cannot influence the performance of Banjarmasin City DPRD members. Work ability is the variable that has the dominant influence on the performance of Banjarmasin City DPRD members, because based on the results of the ability test, motivation on performance simultaneously on members of Banjarmasin City DPRD, it is known that the ability variable has the most dominant influence, compared to the motivation variable.